Moluscos marinhos: uma abordagem sistemática e uma caracterização da malacofauna de um paleovale submerso da Plataforma Continental na costa Oeste do Estado do Ceará, Brasil - Lima, Marianny Kellen Silva (2021)
The phylum Mollusca has a growing importance in all areas of the biological sciences, which has led to an increase in research about malacofauna in recent decades. Considering the diversity of the theme, this project aims to analyze the ecological aspects of mollusc assemblages. We verified the state of knowledge of malacology in the marine environment and studied the characterization of the mollusc assemblage associated with a submerged paleovale. The project is divided into two chapters. Chapter 1 represents a systematic review of the literature. Through the PRISMA protocol, this review aims to synthesize the scientific literature published in the last twenty years about malacofauna in the marine environment, identifying which sub-region is being analyzed the most. Chapter 2 characterized the assemblage of benthic molluscs associated with the submerged paleovale of Coreaú, Camocim-CE. The study was carried out with the Van Veen dredger, approximately 3.5 L, in a sample mesh. The results indicate that most publications on malacofauna were carried out in the intertidal region, being considered as marine environment the intertidal regions, continental shelf, slope and estuary. In chapter 2, a total of 100 individuals were found in the sampled grid of the Paleovale do Coreaú. 53 species of molluscs distributed in 3 classes and 30 families were identified. They were classified according to their food guilds in five categories: Micro and Macro Scrapers (MR), Detrimentals (D), Suspension Feeders (AS), Predators (P), Unidentified (NI) and Ectoparasites (E). Paleovale has been subdivided into four regions. The investigated environmental variables influenced the composition and structure of the mollusc assemblage associated with different sub-regions of the Paleovale de Coreaú.